KEARIFAN LOKAL MASYARAKAT LERENG GUNUNG MERAPI DALAM KESIAPAN MENGHADAPI BENCANA ERUPSI MERAPI - , EKO YULIANTO; , Dr. Erwan Agus Purwanto, M. Si, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Eruptions of Mount Merapi volcano disaster is fairly common in the region of Yogyakarta and Central Java. In an effort to handle problems that occur, there are always have a problem and one of them is related to how local wisdom give a contribution towards mitigation. In this reseacrh, researchers used the theory of general disaster and than that was sent in the theory of disaster management and over again pursed into discussions on disaster mitigation. researchers also used the concept of local wisdom and also the relation between local wisdom to disaster mitigation. This study used qualitative research methods with a phenomenological approach to determine the phenomena that occur in the community. In the data collection effort used data collection techniques, observation, interview and documentation techniques. The results showed that in society of Kinahrejo there are have a lot of local wisdom that included local wisdom about local disaster mitigation . But the wisdom is still well preserved until now. Local knowledge gave a good contribution to the authorized agency in disaster risk reduction efforts in the region Kinahrejo hamlet. It was evident from the start a good relationship between the agency with their policy and citizens with their local wisdom to jointly play a role in disaster risk reduction efforts. Recommendations that can be given in the present study is that in disaster risk reduction efforts, the parties play a role in it was not ignored local knowledge as an element of local knowledge related disaster mitigation and if it is can be managed properly it will give a good contribution too. Further, it is going to facilitate effort approach to the community for disaster risk reduction policies more easily accepted by society.